Evaluating the use of meropenem in hematologic patients with febrile neutropenia: A retrospective observational single-cohort study - Stuurman, R.A.; Jong, E.; Godschalk, P.C.R.; Corsten, M.F.; Nagtegaal, J.E. (Mediterranean Journal of Hematology and Infectious Diseases, 2023)
Abstract Objectives The Antibiotic Stewardship Team of Meander Medical Centre (Meander MC) instigated a revaluation of its treatment protocol for hematologic patients admitted with febrile neutropenia. The current hospital protocol advises administering meropenem for 72 hours, followed by antibiotic therapy guided by microbiological cultures. In order to responsibly adjust the current empiric regimen, this study aimed to determine the frequency of bacteria resistant to alternative antibiotics, namely ceftazidime and piperacillin/tazobactam, in both surveillance and diagnostic cultures. Methods This retrospective, observational, single-centre study included adult patients with a hematologic malignancy and febrile neutropenia admitted between October 2018 and June 2021. Collected metadata included patient characteristics, surveillance and diagnostic culture results, and antibiotic use. Results A total of 100 patients were included. One or more bacteria resistant to ceftazidime or piperacillin/tazobactam were identified in blood and urine cultures in seven (7%) and one (1%) patients respectively. Conclusions Our results support the safe reduction of the use of meropenem by changing the empiric treatment protocol for patients with hematologic malignancy and febrile neutropenia. As this study showed a lower resistance frequency to piperacillin/tazobactam than to ceftazidime, this antibiotic is the recommended alternative.